Sacrifice and modern thought - Meszaros, Julia T.; Zachhuber, Johannes (Oxford University Press, 2014)
Leading specialists in theology, anthropology, religious studies and history elucidate the modern debate about sacrifice from interest shown in the 16th century through to the present day. Individual chapters discuss anthropological theories theological controversies, philosophical interpretations, and literary uses of sacrifice.